SURVEY OF PLASMA FERRITIN LEVELS IN PATIENTS WITH PROLONGED FEVER ADMITTED TO BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Description and comparison of plasma ferritin concentrations between groups of inpatients with persistent fever due to infectious and non-infectious causes at Bach Mai Hospital. Methods: A cross-sectional descriptive study was conducted on 60 inpatients with prolonged fever at Bach Mai Hospital from June 2022 to June 2023, compared with 30 healthy individuals undergoing routine health check-ups. Results: The study included 60 patients with prolonged fever, with a mean age of 56.6 ± 2.52 years and a male predominance (58.3%). The mean plasma ferritin level in patients with prolonged fever was 3199.0 ± 795.4 ng/mL (median 1215 ng/mL). Ferritin levels in the infectious group (n=36) were 1602.1 ± 327.1 ng/mL and in the non-infectious group (n=24) at 5594.5 ± 1843.2 ng/mL (p = 0.01). Conclusion: Plasma ferritin is significantly elevated in patients with prolonged fever and differs significantly between infectious and non-infectious causes, suggesting that ferritin may serve as a useful marker in guiding the differential diagnosis of prolonged fever.
Keywords: Plasma ferritin, prolonged fever, fever of unknown origin (FUO), infection